Relaciones fósforo-zinc en tres suelos ácidos de Costa Rica, 2: absorción de los elementos por tomate [Lycopersicon esculentum] en el invernadero. - Gúzman, E; Bornemisza, E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
In a greenhouse experiment with tomato as indicator plant and using three acid, low Zn soils from Costa Rica the effects were studied of four P levels (zero, sufficient to supply 36 ug/ml of available P, twice and four times this amount) and four Zn levels (zero, sufficient to supply 4.5 ug/ml of available Zn, twice and four times this amount) determined by the Diaz-Romeu and Hunter (4) technique. It was observed that P ttli.s the limiting element in all soils and even its highest applications did not reduce Zn absorption. In two soils yields increased up to twice .the reconzended optimium level and for one soil even up to four times this level. The foliar P/Zn ratios varied between 27 and 48 for the optimum production pots and between 16 and 56 for the level of more than 85% of the optimum pro-duction. The zero P plants were characterized by very low productions and P/Zn ratios of less than 15 except in one case. The Zn application increased the absorption of the element proportionally to its application but had no important effect on plant production.